1976
DOI: 10.1159/000123814
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between Brains of a Large and a Small Hystricomorph Rodent: Capybara, <i>Hydrochoerus </i>and Guinea Pig, <i>Cavia</i>;Neocortical Projection Regions and Measurements of Brain Subdivisions

Abstract: Somatic sensory, auditory and visual areas of cerebral neocortex were mapped in anesthetized capybaras using surface macroelectrode-evoked potential recording methods. The cortical motor area was mapped using electrical stimulation methods. The results of these experiments in the largest living rodent were similar to those found for the cortical sensory and motor areas of guinea pigs, a small rodent in a closely related family. The representation of the perioral skin in SI cortex was relatively large in capyba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 7 publications
6
49
0
Order By: Relevance
“…All were embedded in celloidin, sectioned exhaustively, and stained with thionin. For more details see for example Campos and Welker [1976].…”
Section: Methodsmentioning
confidence: 99%
“…All were embedded in celloidin, sectioned exhaustively, and stained with thionin. For more details see for example Campos and Welker [1976].…”
Section: Methodsmentioning
confidence: 99%
“…The interspersed organization found in Glires constitutes a distinct design type also insensitive to V1 size. Orientation columns so far have only been found in large visual areas and may not exist in very (3,4,10,14,15)] (E) Mesozoic and cenozoic macroevolution of extant mammals showing divergence into six major clades: Monotremes, Marsupials, Afrotheria, Xenarthra, Laurasiatheria, and Euarchontoglires, which split into Euarchonta and Glires (11). Eutherian size expansion after the K-T extinction event is indicated on top.…”
mentioning
confidence: 99%
“…Kawamura [1971] has re cently published an analysis of the fissural patterns of the neocortices of 89 domestic cats, which should be of use to investigators of feline neocortical functioning. Variations in the fissural patterns of the capybara [Campos and Welker, 1976], llama , and rock hyrax [Welker and Carlson, 1976] have also been depicted. The present study has revealed a wide variability in the fissural patterns of primate brain specimens and a correlation, at least in some instances, between atypical fissural patterns and functional subdivisions of the cortex.…”
Section: Discussionmentioning
confidence: 90%